DEEP SEA FISH RESOURCES DIVERSITY AND POTENTIAL IN THE WATERS OF WESTERN SUMATERA OF THE EASTERN INDIAN OCEAN - Badrudin Badrudin; Wudianto Wudianto; Ngurah N. Wiadnyana; Subhat Nurhakim (Research Center for Fisheries, 2006)
The availability of data and information on the diversity and potential of fish resources provide important aspects for exploitation and management.